THE ESSENCE AND STRUCTURE OF THE PEDAGOGICAL SKILLS OF THE TEACHER OF GENERAL EDUCATIONAL DISCIPLINES OF THE INSTITUTION OF VOCATIONAL EDUCATION - Kabysh , Marina (Professional Pedagogics, 2021)
The relevance of the study is determined by society's demand for advanced pedagogy, which ensures the formation and development of the future teacher as a creative person, competent, responsible, able to carry out professional activities at world standards, ready for continuous professional growth, social and professional mobility.Purpose: to study the essence and structure of pedagogical skills of the teacher of general education disciplines of the vocational education institution.Methods: study of scientific sources – to determine the degree of development of the problem; generalization and systematization – to formulate own views on defining the essence of the concept of "pedagogical skills of the teacher of general education disciplines of vocational education"; structural-component analysis – to identify components of pedagogical skills of teachers of general education disciplines of vocational education.Results: the essence and structure of the pedagogical phenomenon "pedagogical skills of the teacher of general education disciplines of the vocational education institution" are determined.Conclusions: pedagogical skills of the teacher of general education disciplines of vocational education are justified as an integrative complex personality trait based on perfect professional and pedagogical competence, and which provides a high level of self-organization of pedagogical activities through synthesis of knowledge, experience, values and qualities of the teacher and creative solution of professionally oriented tasks of students mastering the system of knowledge in the disciplines of general education for the development of key competencies of future skilled workers; five interdependent components of pedagogical skills of the teacher of general education disciplines of the vocational education institution (motivational-value, cognitive, activity, personal-reflexive, creative) are singled out; the prospects of further substantiation of pedagogical factors and conditions of effective formation of pedagogical skills of the teacher of general educational disciplines of the institution of vocational education are determined.
Keywords: professional education; pedagogical skill; professional-pedagogical competence; general educational disciplines